Hugging the Middle - Cuban, Larry (Education Policy Analysis Archives, 2007)
In the last quarter-century and especially the last decade, testing and accountability have come to dominate education policy at the state and national levels. The common concern about the effects of such testing is that it reshapes teaching in the classroom. But such claims do not look at the evidence of deeper classroom structures (the mix of teacher-centered and student-centered practices) in historical context. This article extends historical research in How Teachers Taught (Cuban, 1993) to the present in three metropolitan school districts. While testing and accountability have become more obvious concerns of teachers, the hybridized classroom environment documented in How Teachers Taught have become more pervasive. This article documents this continuing ubiquity and addresses the apparent inconsistency between evidence of a hybridized classroom environment and the unintended consequences of testing and accountability.